2001
DOI: 10.1021/cm001204h
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of SiO2−Al2O3−CaO−P2O5−K2O−F- Glass Ceramics. 2. Time Dependence of Apatite Crystal Growth

Abstract: It is shown that fluorapatite needles formed in SiO 2 -Al 2 O 3 -CaO-P 2 O 5 -K 2 O-Fglasses upon heat treatment at 1200 °C undergo a time-dependent coarsening that fulfills the criteria of Ostwald ripening. Thermodynamic considerations imply that different growth mechanisms (normal and spiral growth) along different crystallographic directions are responsible for the strongly direction-dependent growth rates observed at 1200 °C, leading to an apatiteneedle aspect ratio as large as 15:1 after 15 h at 1200 °C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…The phosphate concentration of the supernatant showed less variations, but an overall trend of decreasing with time was frequently observed, although some samples displayed an opposite trend of increased phosphate content later in the process. This effect is attributed to the dissolution of the glass matrix of the glass-ceramic composite comprising the substrates18.…”
Section: Resultsmentioning
confidence: 99%
“…The phosphate concentration of the supernatant showed less variations, but an overall trend of decreasing with time was frequently observed, although some samples displayed an opposite trend of increased phosphate content later in the process. This effect is attributed to the dissolution of the glass matrix of the glass-ceramic composite comprising the substrates18.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous studies on fluorapatite glass-ceramics, showing the formation of primary Ca-P rich PSDs and secondary Al-P rich PSDs in the parent glass. 3, 17, 23 The primary PSDs later crystallize into fluorapatite during further heat treatment, while the secondary PSDs remain amorphous. It was shown that the size of the fluorapatite crystals is limited by the size of the PSDs and an isometric shape is retained at lower temperatures and for slow heating rates because diffusion rates are low.…”
Section: Discussionmentioning
confidence: 99%
“…In phosphosilicate glass melts, both P 5+ and Si 4+ have high ionic field strength (43.2 and 23.8, respectively) [23], and have strong attraction to oxygen ions in the glass network. When P 2 O 5 concentration is high enough, the competition in attracting oxygen ions between two network-former ions causes amorphous phase separation (APS), i.e., phosphate-and silicate-rich phases [24,25], and hence induces the subsequent crystallization during cooling; this is reflected by the XRD results. As demonstrated by Ryerson and Mysen [26,27], the structural role of P 2 O 5 can change in metal silicate melts, and it depends on the degree of polymerization.…”
Section: Discussionmentioning
confidence: 99%